Polyolefin microporous membrane and separator for cell using the same

KR103031626B1Active Publication Date: 2026-10-13TORAY BATTERY SEPARATOR FILM KOREA LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020220040219
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-31
Publication Date
2026-10-13
Estimated Expiration
2042-03-31

Smart Images

  • Figure 112024133126129-PAT00003
    Figure 112024133126129-PAT00003
  • Figure 112024133126129-PAT00004
    Figure 112024133126129-PAT00004
Patent Text Reader

Abstract

The present invention relates to a polyolefin microporous membrane and a battery separator using the same, and more specifically, to a polyolefin microporous membrane having excellent mechanical strength, thermal stability, and a uniform structure, and a battery separator using the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a polyolefin microporous membrane and a battery separator using the same, and more specifically, to a polyolefin microporous membrane having excellent mechanical strength, thermal stability, and a uniform structure, and a battery separator using the same. Background Technology

[0002] Polyolefin microporous membranes can be used as battery separators in, for example, lithium primary and secondary batteries, lithium polymer batteries, nickel-hydrogen batteries, nickel-cadmium batteries, nickel-zinc batteries, and silver-zinc secondary batteries. Battery separators play a crucial role in terms of battery safety and performance (capacity, output characteristics, cycle life, etc.) by preventing short circuits caused by contact with the positive electrode active material while simultaneously maintaining the electrolyte within their pores to form pathways for ion conduction. Therefore, polyolefin microporous membranes are required to possess excellent mechanical and thermal properties. Furthermore, with the recent trend toward thinning separators to produce high-capacity batteries, higher safety and superior mechanical properties are required for polyolefin microporous membranes, and it is necessary to expand the operating temperature range of the battery to enable safe operation even at higher temperatures.

[0003] For example, Patent Document 1 discloses a polyethylene porous membrane having high strength and low thermal shrinkage, comprising high molecular weight polyethylene and low molecular weight polyethylene.

[0004] In addition, Patent Document 2 discloses a high-strength microporous membrane with reduced thermal shrinkage rate of MD.

[0005] However, in any literature, it is impossible to achieve excellent mechanical properties and thermal stability in high-level areas.

[0006] Recently, with the increase in energy density and miniaturization of lithium-ion secondary batteries, there is a demand for thin-film separators, as well as the ability to safely operate the battery even at high temperatures. The puncture strength of the porous membrane in Patent Document 1 is 6 N / 20 μm (30.1 gf / μm), which is very low compared to the required level of recent times, and it is clear that sufficient mechanical strength cannot be guaranteed when thin-filmed. Furthermore, because high molecular weight and low molecular weight components are mixed, a non-uniform and unstable structure remains, resulting in a decrease in shutdown temperature and a narrowing of the battery's operating temperature range. In addition, the puncture strength of the microporous membrane described in the example of Patent Document 2 is low at 50 gf / g / m², and thermal characteristics in the TD direction, which are important for batteries where the MD direction is fixed, were not considered. These technologies do not meet the recent trend of thin-filming, and the market is demanding microporous membranes that possess higher thermal stability along with fundamentally higher strength. Prior art literature

[0007] Patent Document 1: Republic of Korea Publication No. 10-2020-0060353 A Patent Document 2: Republic of Korea Publication No. 10-2019-0074318 A The problem to be solved

[0008] The objective of the present invention is to solve the problems of the prior art described above by providing a polyolefin microporous membrane having excellent mechanical strength, high thermal stability in the transverse direction (TD), a shutdown temperature usable in a high temperature range, and a uniform structure, which exhibits excellent battery characteristics when used as a battery separator, a method for manufacturing the same, and a battery separator using the same. means of solving the problem

[0009] The inventors, having conducted extensive research to solve the above problem, discovered that the problem can be solved to a higher degree using a polyolefin microporous membrane having a TMA (Thermomechanical Analyzer)-TD thermal shrinkage rate of 0% or less at 130°C, a puncture strength of 85 gf / g / m² or more, and excellent mechanical strength, thermal stability, and a uniform structure even in a thin film, and thus completed the present invention.

[0010] That is, the polyolefin microporous membrane of the present invention is characterized by satisfying the requirements of (I) below.

[0011] (I) The thermal shrinkage rate of TMA-TD at 130 ℃ is 0% or less, and the puncture strength is 85 gf / g / ㎡ or more.

[0012] It is preferable that the above polyolefin microporous membrane satisfies the requirements of (II) below.

[0013] (II) The average flow diameter / maximum pore diameter measured by a perm porometer is 1.4 or less, and the maximum pore diameter is 80 nm or less.

[0014] It is preferable that the above polyolefin microporous membrane satisfies the requirements of (III) below.

[0015] (III) The sum of the longitudinal (MD, Machine Direction) tensile strength and the transverse (TD, Transverse Direction) tensile strength is 5,000 kgf / cm² or more, and the lower of the MD tensile strength or the TD tensile strength is 2,000 kgf / cm² or more.

[0016] It is desirable that the above polyolefin microporous membrane satisfies the requirements of (IV) below.

[0017] (IV) The shutdown temperature is 145 ℃ or higher.

[0018] It is preferable that the above polyolefin microporous membrane satisfies the requirements of (V) below.

[0019] (V) Viscosity Average molecular weight 1.0×10 6 The above ultra-high molecular weight polyethylene is used as the main raw material.

[0020] It is desirable that the above polyolefin microporous membrane satisfies the requirements of (VI) below.

[0021] (VI) Manufactured by a process in which the first stretching ratio is 50 times or less and the second stretching ratio is 1.5 times or more.

[0022] In addition, the polyolefin microporous membrane of the present embodiment may have a porous layer on at least one surface of the polyolefin microporous membrane containing a filler-containing resin solution or a heat-resistant resin solution containing a filler and a resin binder.

[0023] In addition, the battery separator of the present invention is formed using the polyolefin microporous membrane. Effects of the invention

[0024] The polyolefin microporous membrane of the present invention has a TMA-TD thermal shrinkage rate of 0% or less at 130°C and a puncture strength of 85 gf / g / m² or more, and can solve the above problem at a high level as a polyolefin microporous membrane having excellent mechanical strength, thermal stability, and a uniform structure even in a thin film. Specific details for implementing the invention

[0025] 1. Polyolefin microporous membrane

[0026] The polyolefin microporous membrane of the present embodiment has a TMA-TD thermal shrinkage rate of 0% or less at 130°C and a puncture strength of 85 gf / g / ㎡ or more, and can be manufactured into a thin film having sufficient strength and can be suitably used as a separator for a battery with high safety.

[0027] The following describes the embodiments of this model item by item.

[0029] (1) Polyolefin microporous membrane

[0030] The polyolefin microporous membrane of the present invention comprises a polyolefin resin. The polyolefin resin preferably comprises 60 mass% or more of ultra-high molecular weight polyethylene with a viscosity average molecular weight of 1 million or more, more preferably 70 mass% or more, even more preferably 90 mass% or more, and most preferably uses ultra-high molecular weight polyethylene alone, but may include one or more of other polyethylene, polypropylene, or other resin components within a range that does not impair mechanical properties, thermal stability, or structural uniformity.

[0031] Other polyethylene may be a homopolymer of ethylene as well as an ethylene copolymer containing small amounts of other α-olefins such as propylene, butene-1, hexene-1, pentene-1, 4-methylpentene-1, octene, vinyl acetate, methyl methacrylate, or styrene.

[0032] The type of polypropylene is not particularly limited and may be a homopolymer of propylene, a copolymer of propylene with other α-olefins and / or diolefins (propylene copolymer), or a mixture thereof; however, it is preferable to use a homopolymer of propylene for reasons such as mechanical strength and miniaturization of through pores. As the propylene copolymer, either a random copolymer or a block copolymer may be used. As the α-olefin in the propylene copolymer, an α-olefin having 8 or fewer carbon atoms is preferred. Examples of α-olefins having 8 or fewer carbon atoms include ethylene, butene-1, pentene-1, 4-methylpentene-1, octene-1, vinyl acetate, methyl methacrylate, styrene, and combinations thereof. As the diolefin in the propylene copolymer, a diolefin having 4 to 14 carbon atoms is preferred. Examples of diolefins having 4 to 14 carbon atoms include butadiene, 1,5-hexadiene, 1,7-octadiene, 1,9-decadien, etc.

[0033] Specific examples of other resin components include fluorine-containing resins such as polyester, polymethylpentene [PMP or TPX (transferable polymer X), melting point: 230–245 °C], polyamide (PA, melting point: 215–265 °C), polyarylene sulfide (PAS), vinylidene fluoride homopolymers such as polyvinylidene fluoride (PVDF), fluorinated olefins such as polytetrafluoroethylene (PTFE), and copolymers thereof; Examples of heat-resistant resins include polystyrene (PS, melting point: 230 ℃), polyvinyl alcohol (PVA, melting point: 220~240 ℃), polyimide (PI, Tg: 280 ℃ or higher), polyamideimide (PAI, Tg: 280 ℃), polyethersulfone (PES, Tg: 223 ℃), polyetheretherketone (PEEK, melting point: 334 ℃), polycarbonate (PC, melting point: 220~240 ℃), cellulose acetate (melting point: 220 ℃), cellulose triacetate (melting point: 300 ℃), polysulfone (Tg: 190 ℃), and polyetherimide (melting point: 216 ℃). The resin component is not limited to being composed of a single resin component, but may be composed of multiple resin components.

[0034] The viscosity average molecular weight (Mv) of ultra-high molecular weight polyethylene is 1.0 × 10⁻⁶ 6 This is the extent, and preferably 1.2×10 6 3.0×10 6 Below, more preferably 1.5×10 6 2.5×10 6 The following applies. By using ultra-high molecular weight polyethylene within the above range as the main raw material, excellent mechanical and thermal properties and a uniform structure can be formed. Viscosity average molecular weight is 1.0 × 10⁻⁶ 6 Below this level, sufficient mechanical strength may not be achieved. Meanwhile, the viscosity average molecular weight is 3.0 × 10⁻⁶ 6 If ultra-high molecular weight polyethylene exceeding [a certain value] is used as the main raw material, stable extrusion cannot be achieved, which can lead to a deterioration in productivity.

[0036] (2) Characteristics

[0037] (Membrane thickness)

[0038] The thickness of the polyolefin microporous membrane of the present embodiment is preferably 20 μm or less, more preferably 2 to 16 μm, and even more preferably 3 to 14 μm. When the membrane thickness is within the above range, if the polyolefin microporous membrane of the present embodiment is used as a separator for a battery, it can have improved battery capacity and good mechanical and thermal properties. For example, the membrane thickness can be within the above range by appropriately adjusting the discharge amount from the T-die, the rotation speed of the cooling roll, the line speed, and the stretching ratio.

[0040] (Speculation)

[0041] Typically, the physical properties of polyolefin microporous membranes, such as membrane thickness or strength, are adjusted by stretching the microporous membrane. However, the viscosity of the present invention, average molecular weight 1.0 × 10⁻⁶ 6 In the above microporous membrane, if appropriate processing conditions are not implemented, sufficient permeability cannot be secured, and there is a possibility that the performance as a battery may deteriorate. The value calculated as air permeability / membrane thickness is preferably 2 to 40 sec / µm, more preferably 3 to 38 sec / µm, and more preferably 5 to 35 sec / µm. If this value is too low, ion permeability during a short circuit increases, which may cause a risk of ignition, and if this value becomes excessively high, ion permeability during normal operation of the battery decreases, which may degrade output characteristics. The air permeability can be set to the above range by controlling the gel-like sheet, the stretching conditions of the microporous membrane after drying, etc.

[0043] (Maximum respect)

[0044] The polyolefin microporous membrane of the present embodiment has an average flow diameter / maximum pore diameter measured in the order of Dry-up and Wet-up using a pump phorometer of 1.4 or less, preferably 1.38 or less, and more preferably 1.37 or less. In addition, the maximum pore diameter is 80 nm or less, preferably 70 nm or less, and more preferably 60 nm or less. By keeping it within the above range, a dense pore structure with high uniformity of through-pore diameter is obtained. A battery separator having such a pore structure can uniformly disperse the ion passage path in the in-plane direction of the separator. Furthermore, when used as a battery separator, the cycle life of the battery can be improved by suppressing local clogging or dendrite growth. In addition, improvements in battery safety and output characteristics can also be expected.

[0046] (Penetration strength)

[0047] The puncture strength of the polyolefin microporous membrane of the present embodiment is 85 gf / g / m² or higher, preferably 85 to 130 gf / g / m², and more preferably 90 to 125 gf / g / m². If the puncture strength is less than 85 gf / g / m², the mechanical strength when formed into a thin film is insufficient, which may cause self-discharge or spontaneous combustion. On the other hand, if the strength is too high, the membrane cannot be formed stably, and a non-uniform structure may result.

[0049] (Shutdown temperature)

[0050] The shutdown temperature of the polyolefin microporous membrane of the present embodiment is 145°C or higher, preferably 145 to 150°C, and more preferably 145 to 148°C. The shutdown temperature is the temperature at which the performance of the battery is stopped by closing the pores of the microporous membrane when the internal temperature of the battery rises. Due to recent improvements in safety technology, there is a requirement for high-output batteries to operate as batteries over a wider temperature range. Batteries used for a long time at high output may experience internal temperatures rising to around 145°C, and a microporous membrane with a raised shutdown temperature is required to maintain a normal operating state. If the shutdown temperature is below 145°C, the operating temperature range of the battery narrows, which may limit its applications. If the shutdown temperature exceeds 150°C, meltdown may begin simultaneously, making it difficult to safely stop the battery. By setting the shutdown temperature within the above range, the operating temperature range of the battery can be expanded while also ensuring safety.

[0052] (tensile strength)

[0053] The polyolefin microporous membrane of the present embodiment has a sum of MD tensile strength and TD tensile strength of 5,000 kgf / cm² or more, preferably 5,000 to 9,000 kgf / cm², and more preferably 6,000 to 8,000 kgf / cm². In addition, the lower of the MD tensile strength or TD tensile strength is 2,000 kgf / cm² or more, preferably 2,000 to 4,000 kgf / cm², and more preferably 2,000 to 3,000 kgf / cm². By setting the tensile strength to the above range, sufficient puncture strength can be ensured while retaining a certain elongation required for processing.

[0055] 2. Method for manufacturing a polyolefin microporous membrane

[0056] The method for manufacturing a polyolefin microporous membrane of the present embodiment is not particularly limited as long as it can produce a polyolefin microporous membrane having the characteristics described above, and conventionally known methods may be used, for example, methods described in the specifications of Japanese Patent No. 2132327 and Japanese Patent No. 3347835, International Publication No. 2006 / 137540, etc. may be used. Specifically, it is preferable to include the following processes (1) to (7), and may also include the following process (8).

[0057] (1) A process for preparing a polyolefin solution by melt-kneading the polyolefin resin containing ultra-high molecular weight polyethylene and a solvent for film formation.

[0058] (2) A process of extruding the above polyolefin solution to form a sheet, and then cooling to form a gel sheet.

[0059] (3) A first stretching process for stretching the gel sheet above

[0060] (4) Process of removing the film-forming solvent from the gel sheet after stretching.

[0061] (5) A process of drying the sheet after removing the solvent for the above-mentioned film.

[0062] (6) A second stretching process for stretching the sheet after drying.

[0063] (7) A third stretching process for heat-treating the sheet after drying.

[0064] (8) A process of crosslinking and / or hydrophilizing the sheet after the above stretching process

[0065] In particular, in process (1), Mv is 1.0×10 6By making the film-forming solvent mixed with the above-mentioned ultra-high molecular weight polyethylene 70 mass% or more based on the total amount of polyolefin solution and adding the film-forming solvent in two stages, first and second, and making the stretching ratio in process (3) 50 times or less and the stretching ratio in process (6) 1.5 times or more, mechanical strength, thermal stability, and uniform structure formation that could not be achieved in the conventional method can be achieved.

[0067] (1) Manufacturing process of polyolefin solution

[0068] A suitable film-forming solvent is added to the above polyolefin resin, and then melt-kneaded to prepare a polyolefin solution. For example, as a melt-kneading method, a method using a twin-screw extruder as described in the specifications of Japanese Patent No. 2132327 and Japanese Patent No. 3347835 may be used. Since the melt-kneading method is known, a description is omitted.

[0070] (2) Process of forming a gel sheet

[0071] The polyolefin solution is extruded into a sheet form.

[0072] The extrusion method may be either the flat die method or the inflation method. Since both methods are known, a detailed description is omitted. The die gap is 0.1 to 5 mm. The extrusion temperature is preferably 140 to 250 ℃.

[0073] As an extrusion method, for example, the method disclosed in Japanese Patent Publication No. 2132327 and Japanese Patent Publication No. 3347835 may be used.

[0074] A gel-like sheet is formed by cooling the obtained extruded body. As a method for forming the gel-like sheet, for example, the method disclosed in Japanese Patent Publication No. 2132327 and Japanese Patent Publication No. 3347835 may be used. It is preferable to perform cooling at a rate of at least 50°C / min until the gelation temperature is reached. It is preferable to perform cooling down to 30°C or lower. If the cooling rate is within the above range, the degree of crystallization is maintained within a suitable range, resulting in a gel-like sheet suitable for stretching. As a cooling method, methods such as contacting with a refrigerant like cold air or cooling water, or contacting with a cooling roll may be used, but it is preferable to cool by contacting with a roll cooled with a refrigerant. The present invention is not limited to a single layer and may be appropriately applied to multiple layers using known methods.

[0076] (3) First stretching process

[0077] Next, the obtained gel sheet is stretched in at least one axial direction. Since the gel sheet contains a solvent for film formation, it can be stretched uniformly. After heating, it is preferable to stretch the gel sheet by a tenter method, a roll method, an inflation method, or a combination thereof. The stretching may be uniaxial or biaxial stretching, but biaxial stretching is preferred. In the case of biaxial stretching, any of simultaneous biaxial stretching, sequential stretching, and multi-stage stretching (e.g., a combination of simultaneous biaxial stretching and sequential stretching) may be used.

[0078] In this process, the stretching ratio (area stretching ratio) is preferably 2 times or more for uniaxial stretching, and more preferably 3 to 10 times. In the case of biaxial stretching, it is preferably 9 times or more, and more preferably 16 times or more. It is particularly preferable to have a ratio of 25 times or more, but it is not desirable to have a ratio exceeding 50 times because it forms a non-uniform structure. In addition, it is preferable to have a ratio of 3 times or more in either the MD or TD direction, and the stretching ratios in the MD direction and the TD direction may be the same or different from each other. If the stretching ratio is 9 times or more, an improvement in puncture strength can be expected. Furthermore, the stretching ratio in this process refers to the area stretching ratio of the microporous membrane immediately preceding the process, based on the microporous membrane immediately preceding the process, provided to the next process.

[0079] The stretching temperature of the process is preferably within the range of the crystal dispersion temperature (Tcd) of the second polyolefin resin to Tcd + 20 ℃, more preferably within the range of Tcd + 2 ℃ to Tcd + 15 ℃, and particularly preferably within the range of Tcd + 3 ℃ to Tcd + 12 ℃. If the stretching temperature is within the above range, excellent mechanical properties, high thermal stability, and a uniform hole structure can be formed.

[0080] The crystal dispersion temperature (Tcd) is determined by measuring the temperature characteristics of dynamic viscoelasticity according to ASTM D4065. Since ultra-high molecular weight polyethylene, polyethylene other than ultra-high molecular weight polyethylene, and polyethylene compositions have a crystal dispersion temperature of about 90 to 100 °C, it is preferable to set the stretching temperature to 90 to 120 °C, more preferably to 102 to 115 °C, and even more preferably to 103 to 112 °C.

[0081] Through the stretching described above, cleavage occurs between the polyethylene lamellae, the polyethylene phase is refined, and numerous fibrils are formed. The fibrils form a three-dimensionally irregularly connected network structure. While stretching improves mechanical strength and expands pores, it was possible to control the through-pore diameter and achieve high thermal stability even at thinner film thicknesses by performing stretching under appropriate conditions. For this reason, it is suitable for safer and higher-performance battery separators.

[0082] Depending on the desired physical properties, stretching may be performed by creating a temperature distribution in the film thickness direction.

[0084] (4) Removal of solvent for the tabernacle

[0085] The film-forming solvent is removed (cleaned) using a cleaning solvent. Since the polyolefin phase is phase-separated from the film-forming solvent phase, removing the film-forming solvent results in a porous membrane composed of fibrils forming a fine three-dimensional network structure, having three-dimensionally irregularly interconnected holes (pores). The cleaning solvent and the method for removing the film-forming solvent using it are known, so a description is omitted. For example, the method disclosed in Japanese Patent No. 2132327 or Japanese Patent Publication No. 2002-256099 may be used.

[0087] (5) Drying process

[0088] The microporous membrane from which the film-forming solvent has been removed is dried by a heat drying method or an air drying method. The drying temperature is preferably lower than the crystal dispersion temperature (Tcd) of the polyolefin resin, and in particular, it is preferably 5°C or lower than Tcd. It is preferable to dry the microporous membrane until the residual cleaning solvent is 5% or less with respect to 100% by mass (dry weight) of the microporous membrane, and it is more preferable to dry it until it is 3% or less. If the residual cleaning solvent is within the above range, the porosity of the microporous membrane is maintained when the subsequent stretching and heat treatment processes are performed, and the deterioration of permeability is suppressed.

[0090] (6) Second stretching process

[0091] It is desirable to stretch the microporous membrane after drying in at least one axial direction. Stretching of the microporous membrane can be performed using a tenter method or the like while heating, as described above. Stretching may be uniaxial stretching or biaxial stretching. In the case of biaxial stretching, either simultaneous biaxial stretching or sequential stretching may be performed, but sequential biaxial stretching is preferred.

[0092] The stretching temperature in this process is not particularly limited, but is typically 60 to 140 ℃, and more preferably 80 to 139 ℃.

[0093] In this process, the uniaxial stretching ratio of the microporous membrane is preferably 1.0 times or more, more preferably 1.1 times or more, and even more preferably 1.2 times or more. Additionally, it is preferable that the upper limit is 1.8 times or less. In the case of uniaxial stretching, it is set to 1.0 to 2.0 times in the MD direction or TD direction. In the case of biaxial stretching, the area stretching ratio is preferably 1.0 times or more, more preferably 1.1 times or more, and even more preferably 1.2 times or more. The upper limit is suitable to be 4.5 times or less, and is set to 1.0 to 2.1 times in the MD direction and TD direction, respectively, and the stretching ratios in the MD direction and TD direction may be the same or different from each other. Furthermore, the stretching ratio in this process refers to the stretching ratio of the microporous membrane immediately preceding the process, based on the microporous membrane immediately preceding the process, provided for the next process.

[0095] (7) Heat treatment process (third stretching process)

[0096] The microporous membrane after drying and the second stretching process may be subjected to heat treatment. Through heat treatment, the crystals are stabilized and the lamellae are homogenized. As a heat treatment method, heat fixation and / or heat relaxation treatment may be used. Heat fixation is a heat treatment in which the membrane is heated while maintaining its dimensions. Heat relaxation is a heat treatment in which the membrane is heat-shrinked in the MD or TD direction during heating. It is preferable to perform heat fixation using a tenter method or a roll method. For example, the method disclosed in Japanese Patent Publication No. 2002-256099 can be cited as a heat relaxation method. The heat treatment temperature is preferably within the range of Tcd to Tm of the second polyolefin resin.

[0098] (8) Crosslinking and hydrophilization processes

[0099] In addition, additional crosslinking and / or hydrophilization treatments may be performed on the microporous membrane after bonding or stretching.

[0100] For example, a crosslinking treatment is performed on a microporous membrane by irradiating it with ionizing radiation such as alpha rays, beta rays, gamma rays, or electron beams. In the case of electron beam irradiation, an electron beam dose of 0.1 to 100 Mrad is preferred, and an acceleration voltage of 100 to 300 kV is preferred. The meltdown temperature of the microporous membrane increases due to the crosslinking treatment.

[0101] In addition, hydrophilization treatment can be performed by monomer grafting, surfactant treatment, corona discharge, etc. It is preferable to perform monomer grafting after crosslinking treatment.

[0103] 3. Stacked microporous membrane

[0104] In addition, it is also acceptable to form a laminated porous membrane by creating another layer on at least one surface of the above-mentioned polyolefin microporous membrane. Examples of other layers include a porous layer formed using a filler-containing resin solution or a heat-resistant resin solution containing a filler and a resin binder.

[0105] Examples of the above-mentioned fillers include organic fillers such as inorganic fillers or cross-linked polymer fillers, and it is desirable that they have a melting point of 200°C or higher, high electrical insulation properties, and be electrochemically stable within the usage range of a lithium-ion secondary battery. Examples of such inorganic fillers include oxide-based ceramics such as alumina, silica, titania, zirconia, magnesia, ceria, yttria, zinc oxide, and iron oxide; nitride-based ceramics such as silicon nitride, titanium nitride, and boron nitride; ceramics such as silicon carbide, calcium carbonate, aluminum sulfate, barium sulfate, aluminum hydroxide, potassium titanate, talc, kaolin clay, kaolinite, heloysite, pyrophyllite, montmorillonite, sericite, mica, aimite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand; glass fibers and their fluorides. Examples of such organic fillers include cross-linked polystyrene particles, cross-linked acrylic resin particles, cross-linked methyl methacrylate particles, and fluoropolymer particles such as PTFE. These can be used as a single type or in combination of two or more types.

[0106] The average particle size of the above filler is not particularly limited, but a preferred example is 0.1 μm or more and 5.0 μm or less.

[0107] The proportion (mass fraction) of the above filler in the above porous layer is preferably 50% or more and 99.99% or less in terms of heat resistance.

[0108] As the resin binder, the polyolefin or heat-resistant resin described in the section regarding resin components compatible with the above-mentioned ultra-high molecular weight polyethylene with a viscosity average molecular weight of 1 million or more can be suitably used.

[0109] It is preferable that the ratio of the resin binder to the total amount of the filler and the resin binder be 0.5% or more and 10% or less in terms of the binding properties of both in terms of volume fraction.

[0110] As the heat-resistant resin mentioned above, the same heat-resistant resin described in the section regarding resin components compatible with the above-mentioned ultra-high molecular weight polyethylene with a viscosity average molecular weight of 1 million or more can be suitably used.

[0111] The method of applying the above filler-containing resin solution or heat-resistant resin solution to the surface of the polyolefin microporous film is not particularly limited as long as it is a method capable of realizing the required layer thickness or coating area. Specifically, examples include the gravure coater method, small-diameter gravure coater method, reverse roll coater method, transfer roll coater method, kiss coater method, dip coater method, knife coater method, air doctor coater method, blade coater method, rod coater method, squeeze coater method, cast coater method, die coater method, screen printing method, and spray coating method.

[0112] The solvent of the above filler-containing solution or heat-resistant resin solution is preferably a solvent that is removed from the solution applied to the polyolefin microporous membrane, and is not particularly limited. Specifically, examples include N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, water, ethanol, toluene, xylene, methylene chloride, and hexane.

[0113] The method for removing the solvent is not particularly limited as long as it does not degrade the physical properties of the polyolefin microporous membrane. Specifically, examples include a method of drying the polyolefin microporous membrane at a temperature below its melting point while fixing it, a method of drying under reduced pressure, and a method of immersing it in a solvent of a resin binder or a heat-resistant resin to solidify the resin while simultaneously extracting the solvent.

[0114] The thickness of the above porous layer is preferably 0.5 μm or more and 100 μm or less from the perspective of improving heat resistance.

[0115] In the porous membrane of the present embodiment, the ratio of the thickness of the porous layer to the thickness of the porous membrane can be appropriately adjusted according to the purpose.

[0117] 4. Battery separator

[0118] The polyolefin microporous membrane of the present embodiment can be suitably used in either a battery using an aqueous electrolyte or a battery using a non-aqueous electrolyte. Specifically, it can be preferably used as a separator for secondary batteries such as nickel-hydrogen batteries, nickel-cadmium batteries, nickel-zinc batteries, silver-zinc batteries, lithium secondary batteries, and lithium polymer secondary batteries. Among these, it is preferable to use it as a separator for lithium-ion secondary batteries.

[0119] In a lithium-ion secondary battery, a positive electrode and a negative electrode are stacked through a separator, and the separator contains an electrolyte. The structure of the electrode is not particularly limited, and conventional known structures can be used. For example, it can be an electrode structure in which a disc-shaped positive electrode and a negative electrode are arranged to face each other (coin type), an electrode structure in which a flat plate-shaped positive electrode and a negative electrode are alternately stacked (stacked type), or an electrode structure in which a stacked strip-shaped positive electrode and a negative electrode are wound (wound type).

[0120] The current collector, positive electrode, positive electrode active material, negative electrode, negative electrode active material, and electrolyte used in lithium-ion secondary batteries are not particularly limited and can be used by appropriately combining conventionally known materials.

[0121] Furthermore, the present invention is not limited to the above embodiments and can be implemented with various modifications within the scope of its gist.

[0123] The present invention will be described in more detail by way of examples, but the embodiments of the present invention are not limited to these examples.

[0124] In addition, the evaluation method, analysis method, and materials used in the examples are as follows.

[0126] 1. Evaluation methods, analysis methods

[0127] (1) Film thickness (㎛)

[0128] The thickness of five points within a 95 mm × 95 mm range of the microporous membrane was measured using a contact thickness gauge (Lightmatic VL-50 manufactured by Mitutoyo Corporation) and the average value was calculated.

[0129] (2) Basis weight (g / ㎡)

[0130] The weight w1 (g) of the microporous membrane per square meter was set as the basis weight M1 (g / ㎡).

[0131] (3) Public rate (%)

[0132] The weight w1 of the microporous membrane and the weight w2 of an equivalent non-porous polymer (a polymer with the same width, length, and composition) were compared and measured by the following formula.

[0133] Public rate (%) = (w² - w¹) / w² × 100

[0134] (4) Air permeability (sec / 100 cm³ / 16 µm)

[0135] In accordance with JIS P-8117, the air permeability P1 (sec / 100 cm³) measured by an air permeability meter (manufactured by Asahi Seiko Co., Ltd., EGO-1T) was converted to the air permeability P2 per unit volume using the formula: P2=P1 / M1.

[0136] (5) Maximum pore diameter and average flow pore diameter (nm)

[0137] Measurements were taken in the order of Dry-up and Wet-up using a pump phorometer (manufactured by PMI, CFP-1500A). In the Wet-up, pressure was applied to a microporous membrane sufficiently immersed in a known surface tension Galwick (trade name) manufactured by PMI, and the pore size calculated from the pressure at which air begins to penetrate was set as the maximum pore size.

[0138] For the average flow diameter, the pore size was calculated from the pressure at the point where the curve representing the slope of half of the pressure and flow curves from the dry-up measurement intersects the curve from the wet-up measurement. The following formula was used to convert between pressure and pore size.

[0139] d=C·γ / P

[0140] In the above formula,

[0141] d(㎛) is the pore size of the microporous membrane, and

[0142] γ(mN / m) is the surface tension of the liquid, and

[0143] P(Pa) is pressure, and

[0144] C is a constant.

[0145] (6) Piercing strength (gf / g / ㎡)

[0146] The maximum load was measured when a microporous membrane with a thickness T1 (㎛) was pierced at a speed of 2 mm / sec using a needle with a diameter of 1 mm and a spherical tip (radius of curvature R: 0.5 mm). The measured maximum load L1 (gf) was converted into the maximum load L2 per unit volume using the formula: L2 = L1 / M1 and used as the converted piercing strength.

[0147] (7) Shutdown temperature

[0148] Using an air permeability meter (manufactured by Asahi Seiko Co., Ltd., EGO-1T), the air permeability is continuously measured while increasing the temperature of the supplied air from 30°C at a rate of 5°C / min, and the air permeability is 1.0 × 10⁻⁶ 5 The temperature reached in seconds was set as the shutdown temperature. Also, the temperature was raised, and the air permeability was 1.0 × 10 5 The temperature at which it becomes less than a second was set as the meltdown temperature.

[0149] (8) TMA-TD thermal shrinkage rate (%) at 130 ℃

[0150] Using a thermomechanical analysis device (Seiko Instruments Inc., TMA / SS6000), a test specimen of 10 mm (TD) × 3 mm (MD) was heated from room temperature at a rate of 5 ℃ / min while being pulled in the longitudinal direction of the specimen with a set load, and the shrinkage rate was determined by measuring the dimensional change rate relative to the dimensions at 23 ℃ at 130 ℃. The set load was set to 1 g for microporous membranes with a pore size of less than 8 µm and 2 g for microporous membranes with a pore size of 8 µm or more.

[0151] (9) Viscosity average molecular weight (Mv)

[0152] The Mv of ultra-high molecular weight polyethylene was measured using decalin as the solvent at a measurement temperature of 135 ℃ and calculated from the viscosity [η] using the following formula.

[0153] [η] = 6.77 × 10⁻⁶ -4 MV 0.67

[0155] 2. Examples and Comparative Examples

[0156] (Example 1)

[0157] (1) Preparation of polyolefin solution

[0158] Mv is 1.5×10 6 A mixture was prepared by combining 100 parts by mass of ultra-high molecular weight polyethylene (melting point 135 °C) with 0.2 parts by mass of the antioxidant tetrakis[methylene-3-(3,5-Di-tert-butyl-4-hydroxyphenyl)-propionate]methane.

[0159] 23 parts by mass of the obtained mixture were fed into a twin-screw extruder of the strong mixing type (inner diameter 58 mm, L / D=42), 75 parts by mass of liquid paraffin [35 cst (40 ℃)] were supplied in two stages from the side feeder of the twin-screw extruder, and a polyolefin solution was prepared by melt mixing under conditions of 150 ℃ and 200 rpm.

[0160] (2) Extrusion

[0161] A polyolefin solution was fed from a twin-screw extruder to a T-die and extruded. The extruded body was cooled while being drawn in by a cooling roll at a drawing speed of 2 m / min, with the temperature controlled to 25 ℃, to form a gel-like sheet.

[0162] (3) First stretching, removal of the tabernacle solvent, drying

[0163] A gel sheet was simultaneously biaxially stretched (first stretching) by 5 times in the MD direction and 5.5 times in the TD direction using a tenter stretcher at 104°C. The stretched gel sheet was fixed to an aluminum frame plate measuring 20 cm × 20 cm, immersed in methylene chloride at a temperature of 25°C, and the liquid paraffin was removed by shaking at 100 rpm for 3 minutes, and dried at room temperature.

[0164] (4) Second extension, third extension

[0165] After stretching the dried film 1.45 times in the MD direction from 100 using a batch stretching machine, it was stretched 1.99 times in the TD direction at 130°C (second stretching). After that, relaxation heat setting of 0.9 times in the TD direction was performed at 135°C (third stretching).

[0166] The composition, manufacturing conditions, and evaluation results of the polyolefin microporous membrane produced are listed in Table 1.

[0168] (Examples 2-8 and Comparative Examples 1-5)

[0169] Polyolefin microporous membranes of Examples 2-8 and Comparative Examples 1-5 were prepared under conditions similar to those of Example 1, except that the take-up speed of the cooling roll and the third heat fixing temperature were appropriately adjusted for thickness control and the conditions listed in Tables 1 and 2.

[0171]

[0173]

[0175] 3. Evaluation

[0176] The polyolefin microporous membranes of Examples 1-8 exhibited excellent mechanical strength, thermal stability, and a uniform structure, with a TMA-TD thermal shrinkage rate of 0% or less at 130°C and a puncture strength of 85 gf / g / m² or more. From the above results, it can be confirmed that the microporous membrane according to the present invention is capable of supporting a wide range of battery designs.

[0177] Meanwhile, the polyolefin microporous membranes of Comparative Examples 1-5 exhibited TMA-TD thermal shrinkage rates at 130°C that were outside the range of the present invention, and showed inferior mechanical strength, thermal stability, and non-uniform structure compared to the examples.

Claims

Claim 1 A polyolefin microporous membrane having a TMA-TD thermal shrinkage rate of 0% or less at 130 ℃, a puncture strength of 85 gf / g / ㎡ or more, a sum of MD tensile strength and TD tensile strength of 5,000 kgf / cm² or more, and the lower of the MD tensile strength or TD tensile strength of 2,000 kgf / cm² or more. Claim 2 delete Claim 3 delete Claim 4 A polyolefin microporous membrane having a shutdown temperature of 145°C or higher in claim 1. Claim 5 In claim 1, the viscosity average molecular weight is 1.0×10 6 Polyolefin microporous membrane made primarily of ultra-high molecular weight polyethylene. Claim 6 A laminated porous membrane characterized by having a porous layer on at least one surface of a polyolefin microporous membrane described in any one of claims 1, 4, and 5, the porous layer comprising a filler-containing resin solution or a heat-resistant resin solution comprising a filler and a resin binder. Claim 7 A battery separator characterized by being formed using a polyolefin microporous membrane as described in any one of claims 1, 4, and 5.

Citation Information

Patent Citations

  • Polyolefin microporous membrane, production system thereof, battery diaphragm and electrochemical device

    CN112592500A

  • Polyolefin multilayer microporous film, method for producing same, and cell separator

    KR1020170019348A

  • polyolefin microporous membrane

    KR1020210148239A